Reutilización del bagazo de la caña de azúcar, en la elaboración de tableros y su aplicación en paredes, pisos y cielos falsos. - Jiménez Salinas, Magaly del Carmen (2014)
Excessive production of sugar cane bagasse, both in its production, collection and management and emerging trends focused on the development of new materials from organic waste, lead them to seek constructive alternatives that are friendlier to the environment, a world that increasingly demands an ecological responsibility. In this research, we worked on the development boards from sugarcane bagasse under parameters established by the Ecuadorian legislation in strength, with features to integrate them as new materials in the construction field. The boards proposed are easy to manufacture, the process does not require cooking allowing mitigate environmental impact.